2023
DOI: 10.3390/foods12061160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pomegranate Peel Extract and/or Lactic Acid as Natural Preservatives on Physicochemical, Microbiological Properties, Antioxidant Activity, and Storage Stability of Khalal Barhi Date Fruits

Abstract: The use of natural preservatives in the storage of fresh fruits is a promising approach to healthier and more sustainable food processing. The current study was conducted to evaluate the effect of pomegranate peel extract (PPE) and lactic acid (LA) as natural preservatives on the shelf life of Khalal Barhi date fruits. Physicochemical properties, antioxidant activity, color parameters, texture profile, sensory characteristics, and microbiological quality of date fruits were evaluated during six weeks of cold s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 46 publications
7
16
0
Order By: Relevance
“…The ripening percentage (R p ) of the tested date samples of different treatments varied between 5.9 and 98.7%. As date palm is a climacteric crop, the fruits, after harvesting, are subjected to a series of maturity stages, including chemical and physiological changes, besides the production of the ethylene hormone, which is the main factor responsible for the ripening process (Alqahtani et al, 2023). As shown in the correlation analysis, GAC, DT, and ST exhibited significant effects (p < 0.05) on the R p , whereas Ct, AFR, HOL, LT, and Dt revealed insignificant effects (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ripening percentage (R p ) of the tested date samples of different treatments varied between 5.9 and 98.7%. As date palm is a climacteric crop, the fruits, after harvesting, are subjected to a series of maturity stages, including chemical and physiological changes, besides the production of the ethylene hormone, which is the main factor responsible for the ripening process (Alqahtani et al, 2023). As shown in the correlation analysis, GAC, DT, and ST exhibited significant effects (p < 0.05) on the R p , whereas Ct, AFR, HOL, LT, and Dt revealed insignificant effects (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…(1) the natural ripening processes of dates (the conversion from Khalal to Rutab and Tamr stage) include an increase in CO2 and ethylene production, which can lead to degradation of natural pigments and formation of a dark color (Alqahtani et al, 2023); (2) with prolonged storage, the conversion of sucrose to reducing sugars due to natural ripening process may contribute to the change in fruits' color into light brown (Siddiq et al, 2013); (3) the oxidative enzymes such as polyphenol oxidase, peroxidase, and catalase could be responsible for the discoloration and browning through the oxidation of endogenous phenols into quinones (Ghafoor et al, 2022;Taher et al, 2022). In the present study, the minor changes in ΔE* observed in coated samples with an optimized ultrasonic system reflect a delay in ripening, which could be due to the improved barrier properties of the developed coating and its ability to modify the respiration and ethylene production rates of dates, which, in turn, slowed down the fruit's metabolism (Asgarian et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Jiang et al [46] reported that the coating of blue berries with chitosan did not affect negatively on the avor attribute. Alqahtani et al [47] found that the dipping of Barhi date fruits in PPE maintained sensory characteristics during storage period.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…Powder was made from the freeze-dried samples by using a mincer (FOSS Cemotec minced, Germany), and the powder was stored at 40°C until usage. Dry powder was mixed with distilled water (50-g dry solids/100 mL) and stored at 4°C until utilized [20]. All groups of rats were abandoned 1 week after the experiment with no treatment.…”
Section: Preparation Of the Green Tea Extract Gt (Alwazah Swanmentioning
confidence: 99%